Hydrologie et production agricole dans le nord-ouest de l’Amazonie - Josyane Ronchail; Tatiana Schor; Manon Sabot; Heitor Pinheiro; Naziano Filizola; Percy Gomez; Guillaume Drapeau; Véronique Michot; Jean-Loup Guyot; Jean-Michel Martinez; Benjamin Sultan (Bulletin de l’Association de Géographes Français)
In the northwestern Amazon basin, the low water period favors flood recession farming on large emerging fertile surfaces on the river banks and in the inundations plains. The variability of hydrological extremes and of the structure of the flood recession cycle are analyzed in the fluviometric Tamshiyacu station on the Amazonas River, as they are considered as important for the crop quality. Rice cropping which is a profitable activity in this region is neither related to the duration of low-waters, nor to the speed of the rising water. But this work show that since 1985, low water levels have decreased while the duration of the low water period has increased. Moreover, there has been an acceleration of the speed of the water rising.